The ghost of Maurice at the court of Heraclius - Booth, Phil (Byzantinische Zeitschrift, 2019)
This paper explores the complex reception of the reign of Maurice (582-602) at the court of Heraclius (610 -641). It explores how the reign of Maurice established two important precedents for Heraclius as he emerged from the Last Great War: first, the re-establishment, after a long hiatus, of the principle of filial succession; and second, the realisation of a profound, co-operative peace with the Persians. It then argues, however, that Heraclian authors - in particular Theophylact Simocatta - resisted the sanctification of the murdered emperor, framing him instead as, ultimately, a failure, suggesting that he had deserved and accepted his death, and insisting that he had surrendered all of his children, including his son and co-emperor Theodosius, to the same fate. Thus the reign of Maurice was presented not as an apex from which his successors had fallen, but as a pale foreshadowing of the early triumphs of Heraclius.null